Expression profiles of proto-oncogene TWIST1 and tumor metastasis suppressor gene LASS2 in bladder cancer - Yegin, Zeynep; Aydin, Oguz; Koc, Haydar; Buyukalpelli, Recep (Cellular and Molecular Biology, 2018)
Transcription factor proto-oncogene TWIST1 and tumor metastasis suppressor gene LASS2 have been reported to be involved in various carcinomas but their expression profiles and prognostic significances in bladder cancer are largely unknown. We aimed to determine these genes' expression levels both at mRNA and protein level in bladder cancer. mRNA expression levels of TWIST1 and LASS2 genes were examined using real-time quantitative PCR (qPCR) in human bladder tumors and paired normal adjacent tissues obtained from 44 patients. Protein expression profiles of both genes were detected by immunohistochemical staining in formalin-fixed and paraffin-embedded tissues from the same patients. The expression profiles of TWIST1 mRNA in bladder tumors were significantly lower than the normal adjacent tissues and linked to both the stage and the grade. The expression profiles of LASS2 mRNA in bladder tumors were also significantly lower than the normal adjacent tissues reflecting the potential tumor suppressor profile of the gene, independently from stage or grade. By immunohistochemistry, TWIST1 and LASS2 positive expression rates were found as 14.3% (6/42) and 38.1% (16/42), respectively. As potential molecular markers for bladder carcinoma, both TWIST1 and LASS2 transcripts seem to play role during the tumorigenesis and development of bladder cancer. Lack of a functional link and/or weak inverse link between TWIST1 and LASS2 transcripts and immunohistochemical findings may reflect the potential associations of transcription regulation mechanisms and merit further investigations. To the best of our knowledge, this is the first report investigating the combined expression profile of TWIST1 and LASS2 in bladder cancer both at mRNA and protein level.